Clustering of maxillary dental arches in relation to stock impression tray design / Mahmuda Momi - Mahmuda, Momi (2015)
The study grouped Malay dental arches into clusters of shapes and sizes by applying the agglomerative hierarchical clustering (AHC) method, with the purpose of providing measurements for designing stock impression trays. Maxillary casts of 82 fully dentate subjects were used as control casts to group the arches. Eighteen variables, related to the length, breadth and palatal depth in each cast were measured. The lengths and widths were measured using Mitutoyo digimatic callipers and palate depths were measured using Mitutoyo digimatic indicator. Values of the 18 variables were subjected to normality tests and the AHC method was applied to establish clusters of dental arches. Forty one test casts were used to verify the defined clusters. Using mean and standard deviation values of the variables in each control cluster along with space for impression materials, three impression trays were designed. The sizes of test arches in each cluster were then compared with the dimensions of the stock tray calculated for each cluster. The amount of space for impression material in each tray was determined. Dental arches in the study were grouped into 3 feasible clusters: Cluster 1 (39.0%), Cluster II (46.3%) and Cluster III (14.6%). The length of the calculated trays provided adequate or optimal space (between 2mm and 9 mm) for impression material in Clusters I and II: 68.7% in Cluster I and 81.2% in Cluster II. However, the tray was too short (less than 2 mm of space) for 55.6% of the casts in Cluster III. The anterior width of all trays at the (canine region) provided optimal space for all (100%) of the casts in all clusters. The posterior width (at the first molar region) provided optimal space for all (100%) of the casts in Cluster II and III, and 93.8% of the casts in Cluster I. Two palate depths are required for each stock tray (shallow and deep), as every cluster had casts with deep and shallow palate depths. The calculated palate depth (deep) accommodated adequate or optimal space for all (100%) of the casts in Cluster I and Cluster II. However, there was inadequate space for the impression material (< 2 mm) iv in 22.2% of the casts in Cluster III. Lowering the height of the palate depth of all trays by 4 mm (shallow) provided optimum space for 37.5% casts in Cluster I, 62.5% in Cluster II and 66.6% in Cluster III. However, there were 62.5% casts in Cluster I, 37.5% in Cluster II and 33.3% casts in Cluster III with too much space for the impression material (> 9 mm). In conclusion, the Malay dental arches may be grouped into 3 clusters. The estimated lengths and widths of the trays provided adequate space for impression materials. However two palate depths need to be incorporated in each tray to accommodate the deep and shallow palates present in each cluster of the Malay ethnic group.